Understanding future skills and enriching the skills debate - Behrend, Clara R.; Götting, Adrian; Kohlgrüber, Michael; Pomares, Egoitz; Wright, Sally (Technische Universität Dortmund, 2022)
This 3rd report of the Deliverable 6.1 builds on the framework for future skills and the skills categorisation developed in the 1st and 2nd reports of the Deliverable 6.1. The report focuses on empirical results of the Beyond 4.0 project on the topic of skills within the digital transformation. It draws from the range of empirical data collected during the qualitative research undertaken in Work Packages 4 and 8 of the BEYOND 4.0 project by identifying illustrative examples exemplifying the impact of digitalisation on the five categories of the aforementioned skills categorisation, presents and discusses the findings along the lines of skills demand and skills supply-sides issues, and accordingly, presents a number of recommendations for policymakers.
Deliverable 6.1 - 3rd report
Keywords: Skills; Skill requirements; Skill demands; Skill categorisation; Future skills; Skills debate; Competences; Digital transformation; Skill supply; Interacting skills; Future of work; 300; Kompetenz; Digitalisierung; Arbeit; Zukunft